Characterization of MSWI fly ash through mineralogy and water extraction - Bayuseno, Athanasius P.; Schmahl, Wolfgang W. (Resources, conservation and recycling, 2011)
This paper investigates the mineralogical characteristics of fresh, aged and hot water extracted MSWI fly ash for providing the baseline information of minerals stability which controls the released heavy metals into the environment. Quantitative determination of bulk phase abundance in the fresh fly ash by the XRD Rietveld refinement method provided composition levels for amorphous and crystalline phases such as potassium tetrachlorozincate (K 2ZnCl 4), gehlenite, halite, quartz, anhydrite, and feldspar. The minerals association in the fly ash is clearly unstable and subject to mineralogical reactions. The phases of K 2ZnCl 4, halite and anhydrite in the fresh fly ash were involved in hydration and dissolution/precipitation processes to form new minerals such as the Zn-bearing mineral gordaite, syngenite, gypsum and hydrocalumite. The solubility-controlling phases and extractability of heavy metals were examined in a Soxhlet hot water-extractor. Here the soluble salts were simply removed from fly ash while Ca-, Al-, Si- and SO 4 2−-bearing hydrate minerals were precipitated from the extraction solution. Furthermore, a low release of heavy metals Zn, Pb and Cd in hot water was noticed, indicating a strong retention of the trace metals in the mineral phases remaining in the insoluble fly ash residues.